Evaluation of antidiabetic activities of linseed (linum usitatissimum l.) Sprout extracts in adult Streptozotocin-induced (a-stz) long-evan rats - Abedin, Mohammad Zakerin; Jarin, Laila; Khan, Mala; Shilpi, Rasheda Yasmin (Bangladesh Journal of Botany, 2024)
The study investigates the anti-diabetic properties of linsseed (Linum usitatissimum L.) sprout extracts in adult streptozotocin (STZ)-induced Long-Evan rats, addressing the limitations of existing treatment strategies in Bangladesh. The diabetic rats were administered orally with 400 mg/kg body weight of methanolic extracts of linseed sprout with a lab diet and glibenclamide as a positive control. Blood sugar levels were measured before, after, and after STZ injection in Long- Evan rats. The lipid profiles and liver function tests were performed. Administration of extracts of linseed sprouts and a standard anti-diabetic drug reduced the glucose level from 9.1 mmol/l to 6.0 mmol/l and 10.5 mmol/l to 6.6 mmol/l , respectively. The study also showed a healthy level of liver function tests and lipid profiles. The in vivo analysis of the potential antidiabetic activity of linseed sprouts in the STZ-induced diabetic mouse model might be used to treat and manage diabetes. Bangladesh J. Bot. 53(3): 503-510, 2024 (September)